2021
DOI: 10.1186/s12885-021-08477-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features of TDO2 overexpression in renal cell carcinoma

Abstract: Background Tryptophan 2,3-dioxygenase (TDO2) is the primary enzyme catabolizing tryptophan. Several lines of evidence revealed that overexpression of TDO2 is involved in anoikis resistance, spheroid formation, proliferation, and invasion and correlates with poor prognosis in some cancers. The aim of this research was to uncover the expression and biofunction of TDO2 in renal cell carcinoma (RCC). Methods To show the expression of TDO2 in RCC, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In ccRCC, interference with TIM-3 protein expression can attenuate the invasion ability by aggravating anoikis ( Yu et al, 2017 ). Knockdown of anoikis-related protein Tryptophan 2,3-dioxygenase (TDO2) inhibits the proliferation and invasion of RCC cells and may be a promising marker for RCC targeted therapy ( Pham et al, 2021 ). Quinazolines trigger anoikis in RCC by targeting the focal adhesion survival signaling, resulting in potent antitumor effects ( Sakamoto et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In ccRCC, interference with TIM-3 protein expression can attenuate the invasion ability by aggravating anoikis ( Yu et al, 2017 ). Knockdown of anoikis-related protein Tryptophan 2,3-dioxygenase (TDO2) inhibits the proliferation and invasion of RCC cells and may be a promising marker for RCC targeted therapy ( Pham et al, 2021 ). Quinazolines trigger anoikis in RCC by targeting the focal adhesion survival signaling, resulting in potent antitumor effects ( Sakamoto et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, experimental evidence suggested a direct effect of TDO on tumor cell survival and proliferation. Moreover, we and others have shown that it promotes growth, migration, and invasiveness of cancer cells, including melanomas ( Pham QT. et al, 2021 ; Cecchi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…In Pham’s study ( Pham Q. T. et al, 2021 ), TDO was shown to be up regulated in bladder cancer cells, stimulating their growth and invasiveness. Interestingly, TDO was found to be necessary for spheroid formation in these cells, suggesting that it could be a potential marker for targeted therapy in bladder cancer ( Pham QT. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TDO2 was shown to overexpress in liver metastases from UVM and may be related to metastatic potential [33]. TDO2 expression was upregulated in renal cell carcinoma and was associated with worse outcomes [34]. These results imply that aberrant TDO2 expression plays a vital role in the development of cancer.…”
Section: Discussionmentioning
confidence: 95%